2022
DOI: 10.3390/cancers14225636
|View full text |Cite
|
Sign up to set email alerts
|

SNP-Target Genes Interaction Perturbing the Cancer Risk in the Post-GWAS

Abstract: Cancer ranks as the second leading cause of death worldwide, and, being a genetic disease, it is highly heritable. Over the past few decades, genome-wide association studies (GWAS) have identified many risk-associated loci harboring hundreds of single nucleotide polymorphisms (SNPs). Some of these cancer-associated SNPs have been revealed as causal, and the functional characterization of the mechanisms underlying the cancer risk association has been illuminated in some instances. In this review, based on the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 150 publications
(131 reference statements)
0
15
0
Order By: Relevance
“…Much evidence suggests that they alter an individual’s genetic susceptibility to cancer by regulating gene expression. [ 46 ] Mutations are irreversible variants in DNA that essentially include spontaneous or non-spontaneous mutations in the human genome. Most mutations are disease-causing in nature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Much evidence suggests that they alter an individual’s genetic susceptibility to cancer by regulating gene expression. [ 46 ] Mutations are irreversible variants in DNA that essentially include spontaneous or non-spontaneous mutations in the human genome. Most mutations are disease-causing in nature.…”
Section: Discussionmentioning
confidence: 99%
“…Since mutations are influenced by both environment and genetics, the distribution of snp and mutations is region-specific and race-specific. [ 46 , 47 ] SMAD7, as an inhibitor of the TGF- β signaling pathway, blocks TGF- β signaling through a negative feedback loop, and due to this inhibitory function, SMAD7 can antagonize a variety of TGF-beta-regulated cellular metabolic processes, for instance, cell proliferation, cell differentiation, apoptosis, adhesion, and migration, then impacting CRC progression. [ 3 , 5 , 48 ] By including the maximum number of case–control studies to date, this analysis also consistently concluded that both the T allele of rs12953717 and the C allele of rs4464148 increased the risk of CRC whereas high expression of the C allele of rs4939827 reduced the risk of CRC.…”
Section: Discussionmentioning
confidence: 99%
“…The human genome suffers multiple and varied injuries. Still, the rate of mutations remains relatively low due to the intervention of DNA repair mechanisms that recognize the damage that has occurred in the DNA structure [ 10 ].…”
Section: Single Nucleotide Polymorphism and Thyroid Cancermentioning
confidence: 99%
“…The co-existence of pTERT and the BRAF V600E mutation is associated with an unfavorable prognosis, distant metastases, and increased mortality [ 8 , 9 ]. As opposed to genetic mutation, which is defined as any abnormal change in a DNA sequence, a genetic polymorphism is a DNA sequence variation commonly found in the population [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…SNPs are probably considered prospective diagnostic and therapeutic biomarkers in cancer [ 8 ]. In a gene, SNPs can be located at promoter regions, exons, introns, or even at 5′- and 3′ UTR, so they can alter the gene expression [ 9 , 10 , 11 , 12 , 13 ]. SNPs present in long noncoding RNAs (lncRNAs) are reported to be associated with cancer risk as they may change the structure and expression levels of lncRNA [ 14 ].…”
Section: Introductionmentioning
confidence: 99%